Geotechnical Responses of Soils and Nearby Structures to Deep Excavations: Review and Case Study Analysis - Maryam Gaber,; Jamal Alsharef,; Salah Hamuda,; Ashref Alzawi,; Nour Alhuda Mansour, (AlQalam Journal of Medical and Applied Sciences, 2026)
Deep excavation projects within city environments often provoke significant shifts in the earth's mass, particularly in stratified layers containing weak soils such as; silty sand and soft clay, which can pose risks to neighboring structures. This article presents a comprehensive review of the application of spatial variability in tunneling and deep excavation and provides useful references in understanding the degradations and damage generated by excavation methods. The paper also presents a two-dimensional finite element analysis of a deep excavation supported by sheet piles, recently constructed in Tripoli, Libya, using the code PLAXIS 2D. The research integrates computer simulations with real-world observations to understand how soil and built structures interact during excavations. Findings of the study reveal that the way the ground deforms depends heavily on soil characteristics, layered formations, the shape of the excavation, and the construction techniques employed. Besides, a 2D soil model effectively simulates the complex behavior between soil and neighboring structures. Furthermore, previous works have proven that the performance of tunnels and deep excavations can be better captured by considering the spatial variability and compared with conventional deterministic analysis methods. Nonetheless, current research still faces many factual scientific problems. Therefore, this paper identifies some research gaps, as well as some recommendations and proposals for future work. Ultimately, the study highlights the importance of developing better predictive tools and practical techniques to carry out deep excavations safely, efficiently, and sustainably within urban settings.